FEMINIST INTERPRETATION OF THE QURAN AS AN IDEOLOGICAL CRITIQUE AGAINST PATRIARCHY (AN INDONESIA CONTEXT) - Farid Muttaqin (LIPI Press, 2015)
My goals in writing this paper are, the first, to analyze and understand the methodology the Muslim feminists apply in their project of reinterpretation of the Quran. I will discuss their understanding of text and contexts, textual and contextual methods of interpretation. I will elaborate of how their method of contextual interpretation reflects their ideological perspective of feminism as a counter-patriarchal culture. I will see how the method of contextualization is in fact another literal approach since this method cannot escape from the important position of text. The second is to examine the impacts of the project in transforming public knowledge and awareness as a sign of ideological change. One of the key objectives of the project is to provide and to comprehend how public response and observe transformation influenced by this project. I will observe in what aspects and levels the project contributes to the ideological transformation from â€œpatriarchyâ€ to gender equal ideology. Keywords : feminist interpretation, interpretation of Quran, patriarchy.